2013
DOI: 10.1371/journal.pone.0072293
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Consequences of Invasive Species: Greenhouse Gas Emissions of Insecticide Use and the Role of Biological Control in Reducing Emissions

Abstract: Greenhouse gas emissions associated with pesticide applications against invasive species constitute an environmental cost of species invasions that has remained largely unrecognized. Here we calculate greenhouse gas emissions associated with the invasion of an agricultural pest from Asia to North America. The soybean aphid, Aphis glycines, was first discovered in North America in 2000, and has led to a substantial increase in insecticide use in soybeans. We estimate that the manufacture, transport, and applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 56 publications
0
35
0
1
Order By: Relevance
“…Whereas reduced-risk programs provide pest control comparable with that of conventional programs, they signiÞcantly reduce concerns about human health and safety, but are more expensive to implement on average (Agnello et al 2009). Reducing the number of pesticide applications can also lower greenhouse gas emissions associated with manufacturing, delivery, and application of pesticides (Heimpel et al 2013). To date, ecological considerationsÑspeciÞcally, effects on a wide range of nontarget beneÞcial arthropodsÑ have not been fully assessed in more realistic Þeld and long-term conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas reduced-risk programs provide pest control comparable with that of conventional programs, they signiÞcantly reduce concerns about human health and safety, but are more expensive to implement on average (Agnello et al 2009). Reducing the number of pesticide applications can also lower greenhouse gas emissions associated with manufacturing, delivery, and application of pesticides (Heimpel et al 2013). To date, ecological considerationsÑspeciÞcally, effects on a wide range of nontarget beneÞcial arthropodsÑ have not been fully assessed in more realistic Þeld and long-term conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, invasions can also indirectly affect GHGs by engaging human activities to control the spread and impacts of invasive species, which has remained largely unrecognized. One recent example revealed that GHG emissions associated with application of pesticides to control invasive Aphis glycines in US agricultural systems can be substantial (Heimpel et al, 2013). Such indirect ways of altering GHGs through human management of invasive species are critical and deserve future attention.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In some cases low residue levels give farmers a preferred partnership with retailers who prefer to buy products with less residues. Furthermore, biological control might contribute to considerable reduction in emission of greenhouse gasses in comparison with pesticide use (Heimpel et al 2013).…”
Section: Viability Of Commercial Biological Control Marketmentioning
confidence: 99%